The growth and rise of Tibet: hidden plate tectonics, 4D evolution of the mantle, and topographic evolution - Papponnier, P (Journal of Nepal Geological Society, 2008)
Results of ongoing studies of Cenozoic deformation and magmatism, coupled with evidence from seismic tomography experiments and the kinematic picture emerging from Holocene slip-rate measurements support a growth model of the 2.5x106 km2 wide and 5000 m high Tibet plateau that reconciles the two most prominent facets of Cenozoic Asian tectonics: relief building and strike-slip extrusion. The rise of the plateau, at the expense of Asian lithosphere, likely occurred in three main stages since India collided with Asia 55Ma ago. It probably involved the successive, northeastward growth and uplift of 3-500 km-wide crustal thrust-wedges, with sediment infill of dammed intermontane basins, in the foreland of mantle megathrusts. The crust thus thickened while the mantle, decoupled beneath gentlydipping decollements, did not. The existence of distinct magmatic belts younging northwards implies that slabs of Asian lithospheric mantle subducted one after another under ranges north of the Gangdese. Reactivation of deep lithospheric cuts corresponding to Mesozoic sutures of the Tibetan collage probably controlled diachronous initiation of subduction from South to North. Oblique subduction of mantle slabs was coupled with extrusion along sinistral faults slicing Tibet’s East side, a slip-partitionning process that accounts for the striking asymmetry of faulting and mountain growth towards the Northeast. Ever since the onset of collision, the Indian plate appears to have overridden its own sinking mantle. Such Indian mantle does not underthrust Tibet much north of the Zangbo suture, which argues against models of plateau build-up involving Indian lithosphere. Tomograms below India confirm that Asian deformation has absorbed at least H?1500 km of convergence since collision began. Beneath NW-Tibet, teleseismic tomography implies that the Tarim lithospheric mantle plunges 45°southwards, down to ~300 km. The thickening crust in Asia appears to hide motions of lithospheric mantle blocks that are similar to those seen at oblique convergent margins. Even in the heart of the collision zone, the continental lithospheric mantle retained enough strength to behave “plate-like”, with deep deformation ocalizing along inherited weak zones. In short, processes operating beneath the largest plateau on Earth may be little more than “hidden Plate Tectonics”. In the mosaic of basins that makes the bulk of the plateau, the evolution of river systems and drainage efficiency, coupled with tectonic uplift provides a robust mechanism to explain systematic regional differences in Tibetan landscape. They also provide a unifying mechanism for the formation of the low-relief interior, and for the origin of the high-elevation low-relief relict surface in SE Tibet. Consequently, they cast doubt on the fashionable contention that a continuous, preuplift, low-relief surface formed at low elevation, all the way to the South China Sea shore, before being warped upwards in the Late Miocene-Pliocene by lower crustal channel flow. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue), p.1